Indihome's New Post Activation Control Application Based On Website With Telegram Features - Mochamad Rifqi Aminudin; Arif Senja Fitrani; Mochamad Alfan Rosid; Sumarno (Procedia of Engineering and Life Science, 2021)
Development of an application to control the activation of new indihome pairs at PT. Telkom Sidoarjo is a necessity that needs to be realized in order to support the performance of helpdesk employees in the process of activating indihome services. In developing the application, a method is needed to be able to design and build applications to meet expectations. Long polling method is one method used to get updates on bots. With the long-polling method, the server will periodically check to the bot whether there are incoming messages. If there is an incoming message, the server will execute based on the request message sent by the user. If there is no message then the server condition is idle (idle). Based on the results of planning, making and testing applications that have been carried out. It was concluded that the Indihome New Install Activation Control Application can input customer data via the SIKPRO bot, check order progress status and the Helpdesk can update order status and provide order feedback through the SIKPRO website. Bots can refuse order requests in case of double requests with the same registration number. Supervisors and Team Leaders can also recap the indihome service activation data based on daily and monthly periods